Modification method of white carbon black, intrinsic flame-retardant white carbon black and flame-retardant composite rubber material

By grafting aluminum hydroxide on white carbon black, the problem of agglomeration of white carbon black in rubber is solved, its dispersion and flame retardant properties are improved, and the mechanical and flame retardant properties of rubber are improved.

CN119775801APending Publication Date: 2025-04-08BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202311289626.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

White carbon black is prone to agglomeration in rubber, resulting in poor dispersion, extended vulcanization time and reduced crosslinking, affecting its reinforcement effect.

Method used

By chemically reacting aluminum hydroxide with the hydroxyl group of white carbon black, aluminum hydroxide is grafted on white carbon black microspheres, reducing the agglomeration behavior of white carbon black and improving its dispersion.

Benefits of technology

The dispersion and flame retardant properties of white carbon black in rubber are significantly improved, and the mechanical properties and flame retardant properties of the rubber matrix are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775801A_ABST
    Figure CN119775801A_ABST
Patent Text Reader

Abstract

The invention relates to an aluminum hydroxide flame retardant, in particular to a modification method of white carbon black, intrinsic flame-retardant white carbon black and a flame-retardant composite rubber material. According to the modification method disclosed by the invention, hydrogen on hydroxyl of the white carbon black is replaced by aluminum hydroxide, so that the aluminum hydroxide is grafted on the white carbon black microspheres by adopting a chemical action, and the occurrence of an agglomeration behavior after the aluminum hydroxide is added into a rubber matrix material is greatly reduced. Therefore, when the intrinsic flame-retardant white carbon black obtained by the modification method disclosed by the invention is used, ideal flame retardance can be achieved only by adding a small amount of the intrinsic flame-retardant white carbon black into a rubber matrix material. In addition, the intrinsic flame-retardant white carbon black obtained by the modification method can effectively improve the mechanical property of a rubber matrix. The modification method disclosed by the invention is simple and convenient in steps, required equipment, such as a stirrer and the like, is relatively common, does not need special environmental conditions, and has large-scale production capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to white carbon black modification, and more particularly to a white carbon black modification method, intrinsic flame retardant white carbon black and flame retardant composite rubber material. Background Art

[0002] White carbon black is a white powder with acidic surface, odorless and tasteless, and has good high temperature resistance and electrical insulation. It is a commonly used rubber reinforcement material. As a rubber reinforcement material, white carbon black can significantly improve the mechanical properties of rubber, but its surface contains a large number of hydroxyl groups, which makes it highly acidic, hygroscopic and hydrophilic. Therefore, when untreated white carbon black is added to rubber, it will easily agglomerate, prolong the vulcanization time, and reduce the degree of crosslinking, thus affecting its reinforcement effect.

[0003] In order to overcome the above shortcomings of silica, the most commonly used method is to modify the surface of silica with silane coupling agents, thereby reducing the surface polarity of silica and increasing compatibility with rubber. However, the traditional sulfur-containing silane coupling agent Si69 requires high mixing temperature during use, which can easily cause rubber scorch and has the disadvantage of high rubber porosity. Summary of the invention

[0004] In view of the deficiencies of the prior art, a method for modifying white carbon black, intrinsic flame retardant white carbon black and a flame retardant composite rubber material are provided.

[0005] When white carbon black is added to rubber as a reinforcing material, there are problems that white carbon black is easy to agglomerate and has poor dispersibility. The modification method of the present invention is to replace the hydrogen on the hydroxyl group of white carbon black with aluminum hydroxide, and to graft the aluminum hydroxide onto the white carbon black microspheres by chemical action, thereby greatly reducing the occurrence of agglomeration behavior after white carbon black is added to the rubber matrix material and improving the dispersibility of white carbon black. In addition, the aluminum hydroxide grafted onto the hydroxyl group of white carbon black is a good flame retardant, so that the modified white carbon black has flame retardancy.

[0006] One of the objects of the present invention is to provide a method for modifying white carbon black.

[0007] The modification method of white carbon black comprises the following steps: dispersing white carbon black with deionized water, adding aluminum salt under stirring conditions, and then dropping alkali solution to obtain a reaction system; stratifying the reaction system, washing the lower layer with deionized water and alcohol in turn, and then drying and grinding to obtain intrinsic flame retardant white carbon black; the alkali solution is a deionized water solution of alkali.

[0008] The present invention is equivalent to modifying white carbon black while preparing aluminum hydroxide. In the process of three hydroxide ions combining with aluminum ions to form aluminum hydroxide, the hydroxyl group on the white carbon black replaces one of the hydroxide ions and combines with the aluminum ion, so that the aluminum hydroxide is grafted on the white carbon black. The volume of the white carbon black particles is much larger than the aluminum hydroxide molecules. Each white carbon black particle has several hydroxyl groups. Therefore, one white carbon black particle can be grafted with several aluminum hydroxide molecules, forming a microstructure in which one white carbon black particle is grafted with several aluminum hydroxide molecules. On the one hand, the hydroxide in the aluminum hydroxide molecule is replaced by white carbon black, so the presence of white carbon black effectively prevents the agglomeration of aluminum hydroxide molecules. On the other hand, the hydroxyl groups on the white carbon black particles are replaced by aluminum hydroxide molecules, and there are no longer hydroxyl groups on the white carbon black particles; therefore, the presence of aluminum hydroxide effectively prevents the agglomeration of the white carbon black particles.

[0009] The white carbon black can be any existing white carbon black. The smaller the particle size of the white carbon black, the better its dispersibility in water, and the better the dispersion performance and flame retardant performance of the prepared intrinsic flame retardant white carbon black. In industrial production, considering the cost, the white carbon black is 100-15000 mesh, preferably 1000-12500 mesh. In some embodiments of the present invention, the white carbon black is 100 mesh or 12500 mesh.

[0010] The aluminum salt serves to provide aluminum ions after being dissolved in water. Therefore, the aluminum salt can be any aluminum salt that is soluble in water, preferably one or both of aluminum chloride and alum. In some embodiments of the present invention, the aluminum salt is aluminum chloride.

[0011] The function of the base is to provide hydroxide ions after dissolving in water. The base is preferably one or more of ammonia water, potassium hydroxide and sodium hydroxide. In some embodiments of the present invention, the base is potassium hydroxide or sodium hydroxide.

[0012] The alkali solution is gradually added dropwise to the reaction system, and therefore, there is no requirement for the concentration of the alkali solution.

[0013] When the aluminum salt is aluminum chloride, the aluminum salt should be added slowly. Otherwise, the liquid temperature will rise rapidly, and even aluminum chloride will splash, which will lead to low grafting rate and poor dispersion of white carbon black. Specifically, it can be added with a spoon, about 0.5g / s.

[0014] The "adding alkali solution dripping" can control the dropping speed to about 5 ml / min. The "adding alkali solution dripping" refers to adding alkali solution dripping until the pH of the reaction system is 7-10. When the pH of the reaction system is 7, theoretically, the aluminum salt is completely reacted, and the aluminum ions are completely grafted to the white carbon black in the form of aluminum hydroxide molecules. Experimental studies have found that the complete reaction of the aluminum salt can only be guaranteed when the alkali solution is added dripping until the pH of the reaction system is 10. If the alkali solution is added dripping until the pH of the reaction system is higher than 10, the alkali solution is wasted, resulting in increased wastewater treatment costs. If the alkali solution is added dripping until the pH of the reaction system is lower than 7, the aluminum salt reaction will not be complete, which will lead to a low grafting rate and poor dispersion performance of white carbon black. In some embodiments of the present invention, the alkali solution is added dripping until the pH of the reaction system is 9.

[0015] The weight ratio of the deionized water to white carbon black is too low, which makes the system in the preparation process too viscous, resulting in the inability of white carbon black to fully contact with the aluminum salt, which in turn leads to fewer grafted white carbon black particles, that is, there are white carbon black particles without grafted aluminum hydroxide, which makes the dispersibility of the product worse and the flame retardancy insufficient. If the weight ratio of the deionized water to white carbon black is too high, the reaction system will be too dilute, and the lower layer product cannot be obtained during the subsequent liquid separation, and the yield will be low. Therefore, in the present invention, the weight ratio of the deionized water to white carbon black is 300-3000:10, preferably 500-2000:10. In some embodiments of the present invention, the weight ratio of the deionized water to white carbon black is 300:10, 500:10, 2000:10 or 3000:10.

[0016] If the weight ratio of the aluminum salt to white carbon is too high, there will be too much aluminum hydroxide not grafted on the white carbon, which will lead to poor dispersion of the product and a significant decrease in the mechanical properties of the rubber. If the weight ratio of the aluminum salt to white carbon is too low, the grafting rate of the white carbon will be too low, that is, the amount of aluminum hydroxide grafted to each white carbon will decrease, which will lead to poor dispersion of the product, very low flame retardancy, and a small decrease in mechanical properties. Therefore, the present invention limits the weight ratio of the aluminum salt to white carbon to 5-10:10, preferably 6-8:10. In some embodiments of the present invention, the weight ratio of the aluminum salt to white carbon is 5:10, 6:10, 8:10 or 10:10.

[0017] The "separating the reaction system into layers" can be performed by static separation or centrifugal separation.

[0018] The drying can be carried out in a vacuum oven at 80°C.

[0019] The above modification method can be carried out at room temperature or in an ice water bath.

[0020] The second object of the present invention is to provide an intrinsic flame retardant silica. The intrinsic flame retardant silica is prepared by the modification method provided in the first object of the present invention.

[0021] The intrinsic flame retardant silica provided by the present invention has the functions of both a flame retardant and a reinforcing agent, and has a good dispersion effect. When aluminum hydroxide is added to a rubber matrix as a flame retardant, its agglomeration behavior causes the effective specific surface area of ​​aluminum hydroxide to be small, and more aluminum hydroxide needs to be added to achieve the ideal flame retardancy. When the intrinsic flame retardant silica of the present invention is used, only a small amount needs to be added to the rubber matrix material to achieve the ideal flame retardancy. In addition, the intrinsic flame retardant silica of the present invention can also effectively improve the mechanical properties of the rubber matrix.

[0022] The third object of the present invention is to provide a flame retardant composite rubber material. The flame retardant composite rubber material is prepared by mixing and vulcanizing raw materials including the intrinsic flame retardant silica provided in the second object of the present invention.

[0023] Specifically, the flame retardant composite rubber material can be made by mixing and vulcanizing raw materials including the following components; each component is calculated by weight: 100 parts by weight of rubber matrix; 30-50 parts by weight of the intrinsic flame retardant silica provided in the second object of the invention, preferably 35-45 parts by weight. The rubber matrix can be any existing rubber matrix. In some embodiments of the present invention, the rubber matrix is ​​natural rubber.

[0024] The raw materials of the flame retardant composite rubber material may also include conventional additives in conventional amounts, such as zinc oxide, stearic acid, antioxidants, accelerators and sulfur in conventional amounts.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention grafts aluminum hydroxide onto white carbon black microspheres by chemical action, so that the contact area between aluminum hydroxide and the rubber matrix per unit volume is greatly increased. White carbon black, as an inorganic silicon dioxide, does not affect the flame retardant effect. White carbon black is a common additive in rubber technology. The grafting of aluminum hydroxide also improves its dispersibility in the rubber matrix, which can effectively improve the mechanical properties of the rubber matrix. The process of the invention does not require dangerous conditions such as high temperature and a pulverizer, and is safer in industrial production.

[0027] The intrinsic flame retardant white carbon black provided by the present invention also has the function of a reinforcing agent, and can be added to the rubber matrix instead of the traditional white carbon black; after being added to the rubber matrix, it can have good dispersibility while eliminating the need for adding a silane coupling agent, thereby making the rubber matrix have good mechanical properties and processing properties. In addition, the intrinsic flame retardant white carbon black provided by the present invention can be added to the rubber matrix instead of the traditional white carbon black, which can greatly improve the flame retardant properties of the rubber.

[0028] When traditional aluminum hydroxide is added to a rubber matrix as a flame retardant, its agglomeration behavior results in a small effective specific surface area of ​​aluminum hydroxide, and too much aluminum hydroxide needs to be added to achieve ideal flame retardancy. The intrinsic flame retardant silica provided by the present invention grafts aluminum hydroxide onto silica microspheres, greatly increasing the specific surface area of ​​aluminum hydroxide. Therefore, adding a small amount can achieve ideal flame retardancy; at the same time, since the hydroxyl groups on the surface of silica are replaced in large quantities, the dispersibility of silica is also greatly improved, which significantly improves the flame retardancy and mechanical properties of the rubber matrix. The intrinsic flame retardant silica provided by the present invention increases the specific surface area of ​​aluminum hydroxide by replacing the hydrogen on the hydroxyl groups of silica with aluminum hydroxide, thereby reducing the volume of aluminum hydroxide required and improving the flame retardant effect and mechanical properties. It is better dispersed in the matrix.

[0029] The modification method of the present invention has simple steps, requires common equipment such as a stirrer, does not require special environmental conditions, and has the ability to be mass-produced.

[0030] In the present invention, unless otherwise specified, the water is deionized water. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic diagram of the structure of the intrinsic flame retardant silica prepared in Example 1; wherein the middle circle represents silica particles;

[0032] Figure 2 This is the FT-IR characterization image of the intrinsic flame retardant silica prepared in Example 2;

[0033] Figure 3 This is a transmission electron microscope image of the intrinsic flame retardant silica prepared in Example 1;

[0034] Figure 4 This is a transmission electron microscope image of the white carbon black used in preparing the intrinsic flame retardant white carbon black in Example 1;

[0035] Figure 5 The torque-time relationship curve diagram of the composite rubber material prepared in Example and Comparative Example 1;

[0036] Figure 6 The stress-strain relationship curve diagram of the composite rubber material prepared in Example and Comparative Example 1. DETAILED DESCRIPTION

[0037] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0038] The reagents used in the following examples and comparative examples are all commercially available products.

[0039] Example 1

[0040] Add 100 mg of 12500 mesh white carbon black to 20 mL of deionized water in a 100 mL beaker, put in a magnet, and then place the beaker on a stirring table to stir. Weigh 60 mg of aluminum chloride and slowly add it to the above beaker with a medicine spoon (about 0.5 g / s) to prevent splashing. Then, 100 mg of potassium hydroxide is prepared into a potassium hydroxide aqueous solution with a concentration of 0.1 mol / mL with deionized water, and the potassium hydroxide aqueous solution is gradually added to the above beaker (the dropping speed is controlled at about 5 ml / min) until the pH is 9; obtain a reaction solution. Subsequently, the reaction solution is centrifuged, the upper clear liquid is poured off, the lower solid is taken out and filtered, and the residual ions are washed off with water and methanol in turn. Finally, the sample after suction filtration is placed in a vacuum oven and dried at 80 ° C. After drying, it is crushed to obtain an intrinsic flame retardant white carbon black of about 10,000 mesh.

[0041] The intrinsic flame retardant white carbon black prepared in this example was dispersed in deionized water at 0.01 g / mL, and then dropped into a copper mesh to obtain Figure 3 Transmission electron micrograph shown.

[0042] Example 2

[0043] Add 100 mg of 100 mesh white carbon black to 30 mL of deionized water in a 250 mL beaker, put in a magnet, and then place the beaker on a stirring table to stir. Weigh 60 mg of aluminum chloride and slowly add it to the above beaker with a medicine spoon (about 0.5 g / s) to prevent splashing. Then, 80 mg of sodium hydroxide is prepared into a sodium hydroxide aqueous solution with a concentration of 0.1 mol / mL with deionized water, and the sodium hydroxide aqueous solution is gradually added to the above beaker (the dropping speed is controlled at about 5 ml / min) until the pH is 9; obtain a reaction solution. Subsequently, the reaction solution is centrifuged, the upper clear liquid is poured off, the lower solid is taken out and filtered, and the residual ions are washed off with water and methanol in turn. Finally, the sample after suction filtration is placed in a vacuum oven and dried at 80 ° C. After drying, it is crushed to obtain an intrinsic flame retardant white carbon black of about 100 mesh.

[0044] The FT-IR characterization of the intrinsic flame retardant silica prepared in this example is shown in Figure 2 shown. Figure 2 In 800nm -1 The Si-O-Al characteristic peaks appearing on the left and right prove that aluminum hydroxide has been successfully grafted onto the surface of silica.

[0045] Example 3

[0046] Add 15g of 12500 mesh white carbon black to 750mL deionized water in a 2L beaker. The solution becomes more viscous and milky white after increasing the proportion of white carbon black. Then put in a magnetic particle, and then place the beaker in an ice water bath and stir to prevent overheating. Weigh 9g of aluminum chloride and add it to the above beaker slowly (about 0.5g / s) with a medicine spoon to prevent splashing. Then dissolve 15g of potassium hydroxide in 400mL deionized water, stir slowly until dissolved, and obtain a sodium hydroxide aqueous solution. Then gradually add (the dropping speed is controlled at about 5ml / min) a sodium hydroxide aqueous solution to the above beaker until the pH is 9; obtain a reaction solution. Centrifuge the reaction solution, pour off the upper clear liquid, take out the lower solid and filter it, and rinse it with water and methanol in turn to wash away the remaining ions. Finally, put the filtered sample into a vacuum oven and dry it at 80℃. After drying, crush it to obtain an intrinsic flame retardant white carbon black of about 10000 mesh.

[0047] Example 4

[0048] Add 50g of 12500 mesh white carbon black to 1500mL deionized water in a 3L beaker and stir until the liquid is milky white. Then put in a magnet and stir the beaker in an ice water bath to prevent overheating. Weigh 30g of aluminum chloride and slowly add it to the beaker with a medicine spoon (about 0.5g / s) to prevent splashing. Then dissolve 50g of potassium hydroxide in 1000mL ice deionized water to neutralize the heat, slowly stir until dissolved, obtain a potassium hydroxide aqueous solution, and then gradually add (the dropping speed is controlled at about 5ml / min) potassium hydroxide aqueous solution to the beaker until the pH is 9; obtain a reaction solution. After standing for 24h, it can be seen that the solution is obviously stratified, the upper clear liquid is poured off, the remaining viscous material is filtered, and the residual ions are washed off with water and methanol in turn. Finally, the filtered sample is placed in a vacuum oven and dried at 80℃. After drying, it is crushed to obtain an intrinsic flame retardant white carbon black of about 10000 mesh.

[0049] Example 5

[0050] Add 100 mg of 12500 mesh white carbon black to 20 mL of deionized water in a 100 mL beaker, put in a magnet, and then place the beaker on a stirring table to stir. Weigh 100 mg of aluminum chloride and slowly add it to the above beaker (about 0.5 g / s) with a medicine spoon to prevent splashing. Then, 150 mg of potassium hydroxide is prepared into a potassium hydroxide aqueous solution with a concentration of 0.1 mol / mL with deionized water, and the potassium hydroxide aqueous solution is gradually added to the above beaker (the dropping speed is controlled at about 5 ml / min) until the pH is 9; obtain a reaction solution. Subsequently, the reaction solution is centrifuged, the upper clear liquid is poured off, the lower solid is taken out and filtered, and the residual ions are washed off with water and methanol in turn. Finally, the filtered sample is placed in a vacuum oven and dried at 80°C, and crushed to obtain an intrinsic flame retardant white carbon black of about 10,000 mesh.

[0051] Example 6

[0052] Add 100 mg of 100 mesh white carbon black to 20 mL of deionized water in a 100 mL beaker, put in a magnet, and then place the beaker on a stirring table to stir. Weigh 50 mg of aluminum chloride and slowly add it to the above beaker with a medicine spoon (about 0.5 g / s) to prevent splashing. Then, 50 mg of potassium hydroxide is prepared into a potassium hydroxide aqueous solution with a concentration of 0.1 mol / mL with deionized water, and the potassium hydroxide aqueous solution is gradually added to the above beaker (the dropping speed is controlled at about 5 ml / min) until the pH is 9; obtain a reaction solution. Subsequently, the reaction solution is centrifuged, the upper clear liquid is poured off, the lower solid is taken out and filtered, and the residual ions are washed off with water and methanol in turn. Finally, the filtered sample is placed in a vacuum oven and dried at 80 ° C, and crushed to obtain an intrinsic flame retardant white carbon black of about 100 mesh.

[0053] Example 7

[0054] Add 100 mg of 12500 mesh white carbon black to 20 mL of deionized water in a 100 mL beaker, put in a magnet, and then place the beaker on a stirring table to stir. Weigh 80 mg of aluminum chloride and slowly add it to the above beaker with a medicine spoon (about 0.5 g / s) to prevent splashing. Then, 100 mg of potassium hydroxide is prepared into a potassium hydroxide aqueous solution with a concentration of 0.1 mol / mL with deionized water, and the potassium hydroxide aqueous solution is gradually added to the above beaker (the dropping speed is controlled at about 5 ml / min) until the pH is 9; obtain a reaction solution. Subsequently, the reaction solution is centrifuged, the upper clear liquid is poured off, the lower solid is taken out and filtered, and the residual ions are washed off with water and methanol in turn. Finally, the sample after suction filtration is placed in a vacuum oven and dried at 80 ° C, and crushed to obtain an intrinsic flame retardant white carbon black of about 10,000 mesh.

[0055] Embodiment 8-14

[0056] A flame retardant composite rubber material is prepared. The formula is 100 parts by weight of natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant, 1 part by weight of accelerator, 2.5 parts by weight of sulfur, and 35 parts of intrinsic flame retardant silica prepared in Examples 1-7. The preparation method is to sequentially add natural rubber, zinc oxide, stearic acid, antioxidant, accelerator, intrinsic flame retardant silica prepared in Examples 1-7, and sulfur into an open mill, and then perform vulcanization at a vulcanization temperature of 140°C.

[0057] Comparative Example 1

[0058] A composite rubber material is prepared. The formula is 100 parts by weight of natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant, 1 part by weight of accelerator, 2.5 parts by weight of sulfur, and 35 parts of white carbon black used in Example 1. The preparation method is to sequentially add natural rubber, zinc oxide, stearic acid, antioxidant, accelerator, white carbon black used in Example 1, and sulfur in an open mill, and then perform vulcanization at a vulcanization temperature of 140°C.

[0059] The aluminum hydroxide modified flame retardant prepared in this comparative example was dispersed in deionized water at 0.01 g / mL, and then dropped into a copper mesh to obtain Figure 4 Transmission electron micrograph shown.

[0060] Compare Figure 3 and Figure 4 It can be seen that white carbon black is very easy to agglomerate, and the intrinsic flame retardant white carbon black has better dispersibility than white carbon black.

[0061] Performance Testing

[0062] The torque-time curve was obtained by a rotorless vulcanization tester. A 2g sample was weighed and tested. During the test, the rotor rotation angle was set to 0.5°, the test frequency was 100 rpm (1.66 Hz), and the test temperature was 150°C.

[0063] The composite rubber materials prepared in Examples 8-14 and Comparative Example 1 were tested by a rotorless vulcanization tester to obtain torque-time curves, such as Figure 5 shown. Figure 5 The torque-time curve of the embodiment is obtained by normalizing the torque-time curves of embodiments 8-14. The length of the vulcanization time is qualitatively determined based on the time when the torque-time curve approaches the horizontal. The size of the crosslinking density is qualitatively determined based on the difference between the start and end of the torque in the torque-time curve. Figure 5 The torque-time curves can be analyzed to show that, compared with the rubber composite material prepared in Comparative Example 1, the vulcanization time of the rubber composite materials prepared in Examples 8-14 is significantly shortened and the crosslinking density is significantly increased.

[0064] The stress-strain relationship curve was obtained by a SANSS universal electronic tensile testing machine. A dumbbell-shaped spline with a width of 6 mm in the middle working area was cut from a rubber sheet with a thickness of 1 mm using a cutter. The thickness at three different positions in the middle working area was measured using a thickness gauge, and the median was recorded as the spline thickness. The test was performed using a universal electronic tensile testing machine with a working interval gauge length of 25 mm and a tensile rate of 500 mm / min. Each sample was measured five times and the median was taken. The tear strength was tested at right angles using the same tensile testing machine. The reaction conditions were the same as those for the tensile test. Each sample was measured five times and the median was taken. The hardness of the rubber was measured using a hardness tester. The spline thickness was 6 mm. Each sample was measured three times and the median was taken.

[0065] The composite rubber materials prepared in Examples 8-14 and Comparative Example 1 were tested by a SANS universal electronic tensile testing machine to obtain stress-strain curves, such as Figure 6 shown. Figure 6 In the embodiment, the stress-strain relationship curve is obtained by normalizing the stress-strain relationship curves of embodiments 8-14. The tensile strength is qualitatively determined based on the difference between the beginning and the end of the stress in the stress-strain relationship curve. Figure 6 It can be analyzed from the stress-strain relationship curve that, compared with the rubber composite material prepared in Comparative Example 1, the tensile strength of the rubber composite materials prepared in Examples 8-14 is significantly improved.

[0066] The test results show that, compared with the rubber composite material without adding the flame retardant, the mechanical properties of the rubber composite material after adding the intrinsic flame retardant silica of the present invention are not reduced, but improved.

Claims

1. A method for modifying white carbon black, characterized in that: The modification method comprises the following steps: After dispersing white carbon black with deionized water, aluminum salt is added under stirring conditions, and then alkali solution is added dropwise to obtain a reaction system; the reaction system is layered, and the lower layer is washed with deionized water and alcohol in turn, and then dried and ground to obtain intrinsic flame retardant white carbon black; the alkali solution is a deionized water solution of alkali.

2. The modification method according to claim 1, characterized in that The white carbon black has a mesh size of 100-15000, preferably 1000-12500.

3. The modification method according to claim 1, characterized in that: The aluminum salt is a water-soluble aluminum salt, preferably one or both of aluminum chloride and alum.

4. The modification method according to claim 1, characterized in that: The alkali is one or more of ammonia water, potassium hydroxide and sodium hydroxide.

5. The modification method according to claim 1, characterized in that: The “adding alkali solution dropwise” refers to adding alkali solution dropwise until the pH of the reaction system is 7-10.

6. The modification method according to claim 1, characterized in that: The weight ratio of the deionized water to the white carbon black is 300-3000:10, preferably 500-2000:

10.

7. The modification method according to claim 1, characterized in that: The weight ratio of the aluminum salt to white carbon black is 5-10:10, preferably 6-8:

10.

8. An intrinsic flame retardant white carbon black, characterized in that: The intrinsic flame retardant silica is prepared by the modification method according to any one of claims 1 to 7.

9. A flame retardant composite rubber material, characterized in that: The flame retardant composite rubber material is prepared by mixing and vulcanizing raw materials including the intrinsic flame retardant silica as claimed in claim 8.

10. The flame retardant composite rubber material according to claim 9, characterized in that: It is prepared by mixing and vulcanizing the following raw materials: Each component is calculated by weight: 100 parts by weight of rubber matrix; 30-50 parts by weight of intrinsic flame retardant white carbon black, preferably 35-45 parts by weight.

Citation Information

Patent Citations

  • Low-smoke flame-retardant rubber compound and preparation method thereof

    CN115109347A

  • Nanometer SiO2 powder dispersion method

    CN1757681A

  • Flame retardant with nanocomplex and method for manufacturing the same

    KR1020170141009A

Cited By

  • Organosilicon high-temperature-resistant wave-transparent high-carbon-formation-rate heatproof coating

    CN121064722A

  • Flame-retardant molded silicone rubber and vulcanization method thereof

    CN121182213A

  • A flame-retardant molded silicone rubber and its vulcanization method

    CN121182213B